Análisis Socioeconómico de la Sostenibilidad de la Cámara de Comercio del cantón Guaranda, provincia Bolívar, periodo 2018-2019 - García Barragán, Yadira Alexandra (2019)
The present titling work allowed the socioeconomic analysis of the sustainability of the Chamber of Commerce located in the Guaranda Province Bolivar Canton, which helps to increase the productivity of the partners and the general society. For the gathering of the information, it was carried out through the interview to the board of directors and surveys of the members, this research is Field, Exploratory and Descriptive. All this is in order to know the existing problems which contributes to determine the current situation of the same through recommendations will be made. To carry out this purpose, a general analysis of the Chamber was carried out defining the philosophy, mission and vision as an indispensable tool in which it is directed towards the future in the short, medium and long term in which it will help to fulfill the objectives of the organization. Subsequently, a plan of socioeconomic analysis of the sustainability of the Chamber of Commerce was executed in which it reflects the economic, social and environmental situation, projects or agreements with other entities benefiting the partners so that their products or services can excel at the level global, provincial and national contributing to it being sustainable and profitable. Keywords: sustainability, socioeconomic analysis, objectives, productivity, environmenta